Terahertz wave energy dissipation body based on pyramid gradient protrusion array and construction method thereof

CN123010158APending Publication Date: 2026-10-30BEIJING HUIYANG SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611201198.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

上述工艺存在以下显著缺陷:第一,加热模压过程往往需要高温高压条件容易破坏柔性多孔基体的原有孔道结构,而且与仿生梯度结构本身采用的致密非柔性材质难以兼容;第二,通过拼接、堆叠或粘贴方式附加的仿生结构层与基体之间属于异质界面,由于热膨胀系数、力学模量等方面存在差异,在弯曲、压缩等动态使用环境下极易产生层间分离;第三,异质界面的存在会对入射太赫兹波造成不必要的界面反射,削弱阻抗匹配效果,降低波能进入材料内部的效率;第四,粘贴或涂覆层与基体的结合力有限,长期使用或反复形变后,仿生结构层容易发生结构脱落,导致器件失效

Benefits of technology

1、通过设置具有棱锥梯度凸起阵列的功能化介孔弹塑体层与预成型的开孔柔性聚合物垫层,并使功能化介孔弹塑体层包括柔性介孔弹塑体基材和在其孔道结构中均匀负载的导电纳米异质体,可以使构建的太赫兹波能耗散体结合多孔材料的轻质弹性、纳米复合的功能性和梯度结构的宽频特性,在太赫兹波段实现了宽频高效衰减,性能优于传统复合材料和单一结构超材料;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123010158A_ABST
    Figure CN123010158A_ABST
Patent Text Reader

Abstract

A terahertz wave energy dissipation body based on pyramid gradient protrusion array and a construction method thereof, the dissipation body comprising: a functionalized mesoporous elastomer layer, including a flexible mesoporous elastomer substrate and a conductive nano-heterostructure; the flexible mesoporous elastomer substrate has a through multi-stage pore structure, a porosity greater than 96%, and a density of 0.015-0.05 g / cm3; the conductive nano-heterostructure is uniformly loaded on the pore surface of the substrate; the pyramid gradient protrusion array includes a plurality of pyramid gradient protrusions arranged in a periodic array; the pyramid gradient protrusion array is formed in situ on the upper surface of the functionalized mesoporous elastomer layer by an ice template method, and is a homologous and homogeneous integrated structure with the functionalized mesoporous elastomer layer; a preformed open-cell flexible polymer pad layer is compounded on the lower surface of the functionalized mesoporous elastomer layer by an interface fusion process. The present application realizes wideband and high-efficiency wave energy attenuation in the 0.1-5.0 terahertz frequency band, and at the same time makes the overall structure have the comprehensive characteristics of ultralight, bendable, compressible and environmental stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of novel electromagnetic functional composite materials technology, specifically relating to a terahertz wave energy dissipator based on a pyramidal gradient protrusion array and its construction method. Background Technology

[0002] Terahertz technology has attracted much attention due to its unique application prospects in imaging, sensing, and communication, and high-performance terahertz wave absorbing or dissipating materials are fundamental to realizing these applications. In traditional solutions, dissipating materials, such as ferrite- or carbon-powder-based composites, while effective at lower frequencies, often face challenges when applied to the terahertz band, including decreased attenuation efficiency, narrow effective bandwidth, high density, and brittleness that makes flexible molding difficult. While metamaterial structures have emerged in recent years and can achieve near-perfect absorption at specific frequencies, their inherent narrowband response characteristics, fabrication complexity, and dependence on rigid substrates limit their practical application in broadband, flexible environments.

[0003] With the development of sustainable materials science, a classic method has emerged to construct biomimetic gradient structures (such as moth eyes and pyramid structures) on the surface of matrix materials to achieve broadband anti-reflection and impedance matching. This method is expected to develop new dissipative materials with broadband bandwidth.

[0004] However, in existing technologies, such biomimetic gradient structures are typically constructed from dense, non-flexible materials (such as rigid polymers, ceramics, or metals), lacking flexible characteristics such as bendability and compressibility, making it difficult to adapt to curved surfaces or dynamic usage environments. Furthermore, when attempting to combine such biomimetic gradient structures with flexible porous substrates, existing technologies typically employ traditional processes such as heat molding, splicing, stacking, or bonding for fusion. The above-mentioned process has the following significant drawbacks: First, the heating and molding process often requires high temperature and high pressure conditions, which can easily damage the original pore structure of the flexible porous substrate, and is also incompatible with the dense, non-flexible material used in the biomimetic gradient structure itself; Second, the biomimetic structural layer added by splicing, stacking, or pasting is a heterogeneous interface with the substrate. Due to differences in thermal expansion coefficients, mechanical moduli, etc., it is very easy for interlayer separation to occur under dynamic usage environments such as bending and compression; Third, the existence of heterogeneous interfaces will cause unnecessary interface reflection of incident terahertz waves, weakening the impedance matching effect and reducing the efficiency of wave energy entering the material interior; Fourth, the bonding force between the pasted or coated layer and the substrate is limited. After long-term use or repeated deformation, the biomimetic structural layer is prone to structural detachment, leading to device failure.

[0005] Therefore, there is still a lack of an improved terahertz wave energy dissipation structure and its construction method that combines the lightweight elasticity of biomass porous materials, the functionality of nanocomposites, the broadband characteristics of biomimetic gradient structures, and the mechanical protection of flexible substrates. Summary of the Invention

[0006] The main objective of this invention is to provide a terahertz wave energy dissipator based on a pyramidal gradient protrusion array and its construction method, so as to stably construct a high-precision micron-level ordered structure on a porous and flexible substrate and ensure the durability of the overall structure under repeated deformation.

[0007] To achieve the above objectives, in a first aspect, the present invention discloses a terahertz wave energy dissipator with a pyramidal gradient protrusion array. The terahertz wave energy dissipator comprises: A functionalized mesoporous elastomeric layer comprises a flexible mesoporous elastomeric substrate and a conductive nanomaterial heterostructure; the flexible mesoporous elastomeric substrate has a through-hole multi-level pore structure, a porosity greater than 96%, a density of 0.015~0.05 g / cm³, preferably 0.02~0.03 g / cm³, and a more preferably porosity of 97%~97.5%; the conductive nanomaterial heterostructure is uniformly loaded on the pore surface of the substrate. The pyramidal gradient protrusion array includes multiple pyramidal gradient protrusions arranged in a periodic array; the pyramidal gradient protrusion array is formed in situ on the upper surface of the functionalized mesoporous elastomeric layer by ice template method, and is an integrated composite structure homologous to the functionalized mesoporous elastomeric layer. A pre-formed open-cell flexible polymer pad is laminated onto the lower surface of the functionalized mesoporous elastomeric layer through an interface fusion process.

[0008] Furthermore, the mesoporous elastomeric substrate is obtained from natural plant stems through delignification treatment; the natural plant stems are balsa wood or poplar wood, with balsa wood being preferred in this invention, as it has higher porosity and excellent toughness, making it less prone to brittle fracture when forming pyramidal structures, and the fiber length-to-diameter ratio after delignification treatment is more suitable for the in-situ assembly process of ice templates.

[0009] Furthermore, the conductive nanoheteromaterial is one or more combinations of carbon two-dimensional nanosheets, one-dimensional carbon nanotubes, conductive polymer nanoparticles, and ferrite nanoparticles. Preferably, a composite of reduced graphene oxide and iron oxide nanoparticles is used, with a preferred mass ratio of 1:2, which achieves synergistic effects on conductivity and magnetic loss in the terahertz band, resulting in optimal broadband attenuation. Alternatively, a composite of carbon nanotubes and iron oxide nanoparticles can be used, with a preferred mass ratio of 1:1. The aforementioned composite of reduced graphene oxide and iron oxide nanoparticles is a preferred embodiment of the present invention.

[0010] Furthermore, the pyramidal gradient protrusions are regular square pyramids or regular hexagonal pyramids, preferably regular square pyramids, which have high process tolerance and regular array arrangement; the diameter of the circumscribed circle of the base of the pyramidal gradient protrusion is 100~500μm, preferably 250~300μm, and the height is 150~600μm, preferably 350~400μm; the array period of the pyramidal gradient protrusion array is the distance between the centers of the bases of adjacent pyramidal gradient protrusions, and the array period is 1.1~1.8 times the diameter of the circumscribed circle of the base of the pyramidal gradient protrusion, preferably 1.2~1.4 times the base size.

[0011] Furthermore, the open-cell flexible polymer pad is melamine-formaldehyde foam or polyurethane foam, preferably melamine-formaldehyde foam; the pad density is less than 0.025 g / cm³, preferably 0.020~0.022 g / cm³; the compression resilience is greater than 90%, preferably 92%~94%.

[0012] Furthermore, the overall thickness of the terahertz wave energy dissipator is 2-8 mm, preferably 3-5 mm, and the surface density is less than 800 g / m², preferably 600-750 g / m²; the average power attenuation rate for vertically incident waves in the 0.5-3.5 THz frequency band is greater than 90%, preferably not less than 93%, and it can withstand 60% compressive strain or a minimum bending radius of 5 mm.

[0013] In a second aspect, the present invention discloses a method for constructing a terahertz wave energy dissipator based on a pyramidal gradient protrusion array as described in the first aspect of the present invention. The method includes the following steps: Prepare a flexible mesoporous elastomeric substrate with a through-hole multi-level pore structure; The mesoporous elastomeric substrate is immersed in a dispersion medium containing conductive nanoheterogeneous material using deionized water as solvent for a predetermined time and then dried to form a uniformly loaded nanoheterogeneous functional phase on the surface of the hierarchical pore structure, thereby obtaining a functionalized mesoporous elastomeric layer; wherein, the concentration of conductive nanoheterogeneous material in the dispersion medium is 0.5~5 mg / mL, preferably 1.5~2.5 mg / mL; A pyramidal gradient protrusion array is constructed on the upper surface of the functionalized mesoporous elastomeric layer using an ice template method; the pyramidal gradient protrusion array comprises multiple pyramidal gradient protrusions arranged in a periodic array. Through interface fusion technology, the lower surface of the functionalized mesoporous elastomeric layer with the pyramidal gradient protrusion array is combined with the pre-formed open-cell flexible polymer pad to form an integrated composite structure. The integrated composite structure is post-processed, including surface modification and configuration stabilization, to obtain the terahertz wave energy dissipator.

[0014] Furthermore, a flexible mesoporous elastomeric substrate with a through-hole multi-level pore structure is prepared, including: The selected natural plant stems are sequentially subjected to delignification treatment and drying to obtain the flexible mesoporous elastomeric substrate. When the selected natural plant stem is balsa wood, the delignification treatment and drying include: The pH of a 1.5-2.5 wt% sodium chlorite aqueous solution was adjusted to 4.5 using glacial acetic acid. The natural plant stems were then added to the adjusted sodium chlorite aqueous solution and treated in a water bath at 75-85°C for 5.5-6.5 hours. After treatment, the stems were removed and repeatedly washed with deionized water until the center was reached to obtain the pre-treated substrate. The pretreated substrate is added to a sodium hydroxide aqueous solution with a mass fraction of 4.5~5.5wt%, and treated in a water bath at 75~85℃ for 1.5~2.5h. After treatment, the substrate is removed, washed with deionized water, and dried to obtain the flexible mesoporous elastomeric substrate.

[0015] Further, the flexible mesoporous elastomeric substrate is immersed in a dispersion medium containing conductive nanomaterials with deionized water as the solvent for a predetermined time and then dried, including: immersing the flexible mesoporous elastomeric substrate in a dispersion medium containing conductive nanomaterials with deionized water as the solvent at room temperature for 12-24 hours, preferably for 12 hours, stirring once every 1.5-2.5 hours during the immersion process to ensure that the pores are fully wetted; after rinsing the surface of the substrate to remove the floating liquid, vacuum drying it at a temperature of 50-70°C for 20-24 hours to complete the functionalization modification.

[0016] Furthermore, a pyramidal gradient protrusion array is constructed on the upper surface of the functionalized mesoporous elastomeric body using the ice template method, including: The flexible mesoporous elastomeric substrate is subjected to high-speed shear homogenization to obtain a fiber component; wherein the high-speed shear homogenization is performed at a rotation speed of 11,000~13,000 rpm for a processing time of 25~35 min; the fiber length of the obtained fiber component is 50~150 μm, preferably 80~120 μm; The fiber component and the conductive nano-heterogeneous phase are dispersed in deionized water to obtain a uniformly suspended composite dispersion. The dispersion process includes: adding sodium dodecylbenzenesulfonate as a dispersant, preferably 0.05 wt% in the composite dispersion; and ultrasonically dispersing for 30 min under ice-water bath conditions to ensure system homogeneity. In the composite dispersion, the concentration of the mesoporous elastomeric fiber component is 0.5-2 wt%, preferably 0.8-1.2 wt%, and the concentration of the nano-heterogeneous functional phase is 0.5-5 mg / mL, preferably 1.5-2.5 mg / mL.

[0017] The upper surface of the functionalized mesoporous elastomeric layer is subjected to plasma activation pretreatment with vacuum degree of 50 Pa, power of 15 W and treatment time of 3 min to improve surface hydrophilicity. Then, the composite dispersion is uniformly coated on the upper surface of the pretreated functionalized mesoporous elastomeric layer by scraping to form a liquid film of a preset thickness. The preset thickness of the liquid film is 200-800 μm, preferably 350-450 μm.

[0018] The coated functionalized mesoporous elastomeric layer is placed on a cold stage with a vertical temperature gradient, allowing ice crystals to grow oriented in a direction perpendicular to the upper surface of the functionalized mesoporous elastomeric layer. During ice crystal growth, the fiber component and the conductive nanomaterial assemble in situ along the ice crystal front to form a pyramidal ice template. The oriented growth temperature gradient is 10-30 °C / cm, preferably 18-22 °C / cm; the cold stage temperature is -20 °C to -80 °C, preferably -35--45 °C; the ice crystal growth rate is 1-10 μm / s, preferably 4-6 μm / s; and the overall freezing time is preferably 60-70 min to ensure complete freezing of the system.

[0019] The pyramidal ice template is freeze-dried and sublimated to remove ice crystals, thereby forming a homogeneous array of pyramidal gradient protrusions in situ on the upper surface of the functionalized mesoporous elastomeric layer. The freeze-drying vacuum is below 10 Pa, preferably 4-6 Pa, and the cold trap temperature is below -50 °C, preferably -55--60 °C. The freeze-drying employs a segmented heating program, including: first, constant temperature drying at -30 °C for 6 hours; then, heating to -10 °C at a rate of 1 °C / h and holding at that temperature for 4 hours; and finally, heating to 25 °C and holding at that temperature for 2 hours to prevent the pyramidal structure from collapsing.

[0020] Furthermore, the open-cell flexible polymer pad is made of melamine formaldehyde foam or polyurethane foam, and the interface fusion can be achieved by hot pressing or adhesive bonding. When hot pressing is used, the preferred process parameters are temperature 120°C, pressure 0.2 MPa, and hot pressing time 5 min. When adhesive bonding is used, water-based polyurethane adhesive is preferred, and the curing time is 24 h at room temperature.

[0021] Compared with the prior art, the beneficial effects of the technical solution of the present invention are as follows: 1. By setting a functionalized mesoporous elastomeric layer with a pyramidal gradient protrusion array and a pre-formed open-cell flexible polymer pad, and making the functionalized mesoporous elastomeric layer include a flexible mesoporous elastomeric substrate and a conductive nano-heterogeneous uniformly loaded in its pore structure, the constructed terahertz wave energy dissipator can combine the lightweight elasticity of porous materials, the functionality of nanocomposite materials and the broadband characteristics of gradient structures, achieving broadband and efficient attenuation in the terahertz band, with performance superior to traditional composite materials and single-structure metamaterials; 2. The pyramidal gradient protrusion array constructed by the ice template method is more firmly bonded to the functionalized mesoporous elastomeric layer than traditional molding methods. Through in-situ growth, a homogeneous integrated composite structure is formed, avoiding interlayer delamination problems, and the process is relatively simple.

[0022] 3. The introduction of flexible pads greatly enhances the mechanical toughness and deformation adaptability of the overall structure, enabling the device to withstand large bending and compression, and is suitable for conformal curved surfaces and dynamic environments.

[0023] 4. The terahertz wave energy dissipator has an extremely low overall density of 0.015~0.05 g / cm³, giving it an excellent weight advantage. Furthermore, its main raw material is derived from renewable biomass, which aligns with the concept of green environmental protection.

[0024] 5. By adjusting the composition of functional nanophases, the geometric parameters of the protrusion array, and the properties of the cushion layer, the operating frequency band and mechanical properties of terahertz wave energy dissipators can be effectively controlled, resulting in high design flexibility. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0026] Figure 1 This is a schematic diagram of the overall three-dimensional structure of the terahertz wave energy dissipator based on a pyramidal gradient protrusion array proposed in this invention. Figure 2 For terahertz waves Figure 1 A schematic diagram of the propagation and attenuation paths in the proposed dissipative structure; Figure 3 A schematic diagram of the surface protrusion array state of a terahertz wave energy dissipator before and after being subjected to compressive deformation; Figure 4 A schematic diagram of the protruding structure of an array of square pyramids and hexagonal pyramids; Figure 5 This is a flowchart of the method for constructing a terahertz wave energy dissipator based on a pyramidal gradient protrusion array according to the present invention. Detailed Implementation

[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0028] It should be noted that all directional indications (such as up, down, left, right, front, back, etc.) in the embodiments of the present invention are only used to explain the relative positional relationship and movement of each component in a certain specific posture (as shown in the figure). If the specific posture changes, the directional indication will also change accordingly.

[0029] Furthermore, in this invention, descriptions involving "first," "second," etc., are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0030] In this invention, unless otherwise explicitly specified and limited, the terms "connection," "fixed," etc., should be interpreted broadly. For example, "fixed" can mean a fixed connection, a detachable connection, or an integral part; it can mean a mechanical connection or an electrical connection; it can mean a direct connection or an indirect connection through an intermediate medium; it can mean the internal communication of two components or the interaction between two components, unless otherwise explicitly limited. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.

[0031] Furthermore, the technical solutions of the various embodiments of the present invention can be combined with each other, but only if they are feasible for those skilled in the art. If the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.

[0032] According to a first aspect of the present invention, a terahertz wave energy dissipator based on a pyramidal gradient protrusion array is proposed.

[0033] Please refer to Figures 1-4 The terahertz wave energy dissipator based on the pyramidal gradient protrusion array has a layered composite structure, which includes, from top to bottom: pyramidal gradient protrusion array 1, functionalized mesoporous elastomeric layer 2 and flexible polymer pad layer 3.

[0034] The functionalized mesoporous elastomeric layer 2 comprises a flexible mesoporous elastomeric substrate and a conductive nanomaterial heterostructure. The flexible mesoporous elastomeric substrate has a through-hole multi-level pore structure with a porosity greater than 96% and a density of 0.015~0.05 g / cm³. The conductive nanomaterial heterostructure is uniformly loaded on the pore surface of the substrate.

[0035] The pyramidal gradient protrusion array 1 comprises multiple pyramidal gradient protrusions arranged in a periodic array. The pyramidal gradient protrusion array is formed in situ on the upper surface of the functionalized mesoporous elastomeric layer by ice template method, and is an integrated composite structure homologous to the functionalized mesoporous elastomeric layer.

[0036] The pre-formed open-cell flexible polymer pad 3 is composited onto the lower surface of the functionalized mesoporous elastomeric layer 2 through an interface fusion process.

[0037] The working process of the terahertz wave energy dissipator under terahertz wave irradiation is as follows: Figure 2 As shown: The incident terahertz wave first arrives at the surface of the pyramidal gradient protrusion array 1. Due to the gradient change in the height of the protrusions, its equivalent wave impedance smoothly transitions from near-air impedance at the top to near-material bulk impedance at the bottom, thus significantly reducing the reflectivity of the terahertz wave at the interface. Most of the wave energy is able to enter the interior of the functionalized mesoporous elastomeric layer 2. In this layer, the terahertz wave encounters a complex hierarchical pore structure and a large number of heterogeneous interfaces composed of nano-heterogeneous functional phases 4 and plant fiber skeletons 5, resulting in strong scattering, multiple reflections, and energy attenuation caused by mechanisms such as interface polarization and conductivity loss. The flexible polymer pad layer 3 mainly provides mechanical support, and its porous structure also has a certain scattering effect on the terahertz wave. When the dissipative body is compressed (e.g. Figure 3 (Illustrative diagram) The flexible pad 3 undergoes significant deformation to absorb stress, while the upper protrusion array 1 and mesoporous elastomeric layer 2, under reasonable design, can maintain structural integrity or undergo synergistic deformation, ensuring the basic stability of the terahertz wave energy dissipation function.

[0038] Because this pyramidal array is formed in situ on the surface of a functionalized mesoporous elastomeric layer using the ice-templating method, it is homologous and homogeneous with the matrix, with continuous fiber continuity and no adhesive or stacking interfaces, thus effectively avoiding interlayer delamination problems and making the process relatively simple. Simultaneously, the loading of conductive nanomaterials inside the pyramids increases continuously from top to bottom, achieving a gradual impedance change within a single pyramid. At the array level, the height of the pyramidal protrusions can be adjusted according to the operating frequency band and mechanical properties of the terahertz wave energy dissipator, thereby achieving an impedance-gradient arrangement at the array scale.

[0039] Furthermore, the mesoporous elastomeric substrate is obtained from natural plant stems through delignification treatment. Preferably, the natural plant stems are balsa wood or poplar wood.

[0040] Further, the conductive nanoheteromaterial is preferably one or a combination of carbon two-dimensional nanosheets, one-dimensional carbon nanotubes, conductive polymer nanoparticles, and ferrite nanoparticles. Preferably, the conductive nanoheteromaterial is a composite of reduced graphene oxide and iron oxide nanoparticles (i.e., rGO / Fe3O4 composite), wherein the mass ratio of reduced graphene oxide to iron oxide nanoparticles is 1:2. Alternatively, preferably, the conductive nanoheteromaterial is a composite of carbon nanotubes and iron oxide nanoparticles, wherein the mass ratio of carbon nanotubes to iron oxide nanoparticles is 1:1.

[0041] Further, the pyramidal gradient protrusion is a regular square pyramid or a regular hexagonal pyramid, the diameter of the circumscribed circle of the base of the pyramidal gradient protrusion is 100~500μm, more preferably 250~300μm; the height of the pyramidal gradient protrusion is 150~600μm, more preferably 350~450μm; the array period of the pyramidal gradient protrusion array is the distance between the centers of the bases of adjacent pyramidal gradient protrusions, and the array period is 1.1~1.8 times the diameter of the circumscribed circle of the base of the pyramidal gradient protrusion, more preferably 1.2~1.4 times.

[0042] Furthermore, the open-cell flexible polymer pad is melamine-formaldehyde foam or polyurethane foam with a density of less than 0.025 g / cm³, more preferably 0.020~0.022 g / cm³; and a compression resilience greater than 90%, preferably 92%~94%. By introducing a low-density and high-resilience flexible pad, the mechanical toughness and deformation adaptability of the overall structure are greatly enhanced, enabling the device to withstand large bending and compression, and making it suitable for conformal curved surfaces and dynamic environments.

[0043] Furthermore, the overall thickness of the terahertz wave energy dissipator is 2~8mm, preferably 3~5mm; the surface density is less than 800g / m², preferably 600~750 g / m².

[0044] Furthermore, the terahertz wave energy dissipator exhibits an average power attenuation rate of over 90% for vertically incident waves in the 0.5–3.5 THz frequency band, an attenuation rate of over 95% in the 1–3 THz frequency band, and an attenuation rate of over 85% at 4 THz.

[0045] Furthermore, the terahertz wave energy dissipator can withstand 60% compressive strain or a minimum bending radius of 5 mm.

[0046] Furthermore, the terahertz wave energy dissipator can be repeatedly compressed (50% strain) 1000 times without structural damage and with electromagnetic performance degradation of less than 5%.

[0047] According to a second aspect of the present invention, a method for constructing a terahertz wave energy dissipator based on a pyramidal gradient protrusion array as described in the first aspect of the present invention is provided. The method specifically includes the following steps: S1. Prepare a flexible mesoporous elastomeric substrate with a through-hole multi-level pore structure.

[0048] This step includes: selecting natural plant stems, sequentially performing delignification treatment and drying to obtain the flexible mesoporous elastomeric substrate. The natural plant stems are preferably balsa wood or poplar stems. Balsa wood has higher porosity and superior toughness compared to poplar or other natural plant stems, making it less prone to brittle fracture when forming pyramidal structures. Furthermore, the fiber aspect ratio after delignification treatment is more suitable for the in-situ assembly process of ice templates.

[0049] When the selected natural plant stem is balsa wood, the delignification treatment and drying include: S11. Adjust the pH of a 1.5~2.5wt% sodium chlorite aqueous solution to 4.5 with glacial acetic acid. Add the natural plant stems to the adjusted sodium chlorite aqueous solution and treat in a water bath at 75~85℃ for 5.5~6.5h. Remove the solution and wash repeatedly with deionized water until neutral to obtain the pretreated substrate.

[0050] S12. The pre-treated substrate is added to a sodium hydroxide aqueous solution with a mass fraction of 4.5~5.5wt%, treated in a water bath at 75~85℃ for 1.5~2.5h, removed, washed with deionized water and dried to obtain the flexible mesoporous elastomeric substrate.

[0051] S2. The flexible mesoporous elastomeric substrate is immersed in a dispersion medium containing conductive nano-heterogeneous material with deionized water as solvent for a predetermined time and then dried to form a nano-heterogeneous functional phase uniformly loaded on the surface of the multi-level pore structure, thereby obtaining a functionalized mesoporous elastomeric material.

[0052] Specifically, in the impregnation process, the impregnation temperature is room temperature, the impregnation time is preferably 12~24h, more preferably 12h, and the impregnation is stirred once every 1.5~2.5h to ensure that the channels are fully wetted.

[0053] After impregnation, the surface liquid of the impregnated substrate needs to be rinsed off, and then vacuum dried at a temperature of 50~70℃ for 20~24h to complete the functionalization modification and obtain a functionalized mesoporous elastomeric body.

[0054] The concentration of conductive nanoheterogeneous material in the dispersion medium is 0.5~5 mg / mL, preferably 1.5~2.5 mg / mL.

[0055] The dispersion medium can be obtained by ultrasonically dispersing conductive nanoheterogeneous materials in deionized water.

[0056] S3. A pyramidal gradient protrusion array is constructed on the upper surface of the functionalized mesoporous elastomeric layer using the ice template method; the pyramidal gradient protrusion array includes multiple pyramidal gradient protrusions arranged in a periodic array.

[0057] Specifically, this step includes the following sub-steps: S31. The flexible mesoporous elastomeric substrate is subjected to high-speed shearing and homogenization treatment to obtain fiber components.

[0058] The high-speed shearing homogenization process involves a rotation speed of 11,000 to 13,000 rpm and a processing time of 25 to 35 minutes. The fiber length of the obtained fiber component is 50 to 150 μm, preferably 80 to 120 μm.

[0059] S32. The fiber component and the conductive nano-heterogeneous body are dispersed in deionized water to obtain a uniformly suspended composite dispersion.

[0060] The dispersion process includes adding sodium dodecylbenzenesulfonate as a dispersant, wherein the amount of the dispersant added to the composite dispersion is preferably 0.05 wt.

[0061] The dispersion process also includes ultrasonically dispersing the composite dispersion under ice-water bath conditions for 30 min to ensure the system is homogeneous.

[0062] Preferably, the concentration of the mesoporous elastomeric fiber component in the composite dispersion is 0.5-2 wt%. % The concentration of the nano-heterogeneous functional phase is preferably 0.8-1.2 wt%; the concentration of the nano-heterogeneous functional phase is 0.5-5 mg / mL, preferably 1.5-2.5 mg / mL.

[0063] S33. The upper surface of the functionalized mesoporous elastomeric layer is subjected to plasma activation pretreatment, and then the composite dispersion is uniformly coated onto the upper surface of the pretreated functionalized mesoporous elastomeric layer by scraping to form a liquid film of a preset thickness.

[0064] Preferably, the pretreatment process involves a vacuum of 50 Pa, a power of 15 W, and a treatment time of 3 min. Pretreatment can improve the hydrophilicity of the upper surface.

[0065] Preferably, the preset thickness of the liquid film is 200-800 μm, and more preferably 350-450 μm.

[0066] S34. The coated functionalized mesoporous elastomeric layer is placed on a cold stage with a vertical temperature gradient, so that the ice crystals grow in a direction perpendicular to the upper surface of the functionalized mesoporous elastomeric layer, so that the fiber component and the conductive nano-heterogeneous body are assembled in situ along the ice crystal front during the ice crystal growth process to form a pyramidal ice template.

[0067] Preferably, the temperature gradient for directional growth is 10-30 °C / cm, more preferably 18-22 °C / cm. Preferably, the cooling stage temperature is -20 to -80 °C, more preferably -35 to -45 °C. Preferably, the ice crystal growth rate is 1-10 μm / s, more preferably 4-6 μm / s. Preferably, the overall freezing time is 60-70 min, more preferably 60 min, to ensure the system is completely frozen.

[0068] S35. Freeze-dry the pyramidal ice template and sublimate to remove the ice crystals in the pyramidal ice template, so as to form a homogeneous pyramidal gradient protrusion array on the upper surface of the functionalized mesoporous elastomeric layer in situ.

[0069] Preferably, the vacuum degree of freeze-drying is below 10 Pa, more preferably 4 to 6 Pa. The cold trap temperature is below -50 °C, more preferably -55 to -60 °C. The freeze-drying process adopts a segmented heating program, including: first, drying at -30 °C for 6 hours, then heating to -10 °C at a rate of 1 °C / h and holding at that temperature for 4 hours, and finally heating to 25 °C and holding at that temperature for 2 hours to avoid the collapse of the pyramidal structure.

[0070] By performing the above steps of the ice template method, a pyramidal gradient protrusion array can be grown in situ on the upper surface of the functionalized mesoporous elastomeric layer, so that the functionalized mesoporous elastomeric layer and the pyramidal gradient protrusion array form an integrated composite structure of the same origin and quality, effectively avoiding the problem of interlayer delamination.

[0071] S4. Through interface fusion process, the lower surface of the functionalized mesoporous elastomeric layer with the pyramidal gradient protrusion array is combined with the pre-formed open-cell flexible polymer pad layer to form an integrated composite structure.

[0072] The open-cell flexible polymer pad is made of melamine-formaldehyde foam or polyurethane foam, and the interface fusion process can be, for example, a hot-pressing fusion process. When using hot-pressing fusion, the preferred process parameters are a temperature of 120°C, a pressure of 0.2 MPa, and a hot-pressing time of 5 min; when using adhesive bonding, a water-based polyurethane adhesive is preferred, and the curing time is 24 h at room temperature.

[0073] S5. Post-process the integrated composite structure, including surface modification and configuration stabilization, to obtain the terahertz wave energy dissipator.

[0074] The configuration stabilization treatment may include drying the integrated composite structure obtained in step S4 in a vacuum drying oven to remove residual moisture and volatiles.

[0075] Surface modification may include: vapor deposition of perfluorodecyltrimethoxysilane on the surface of the stabilized integrated composite structure to form a hydrophobic modified layer and improve environmental stability.

[0076] The above method will be further illustrated below with two specific embodiments and one comparative example.

[0077] Example 1 This embodiment provides a method for constructing a terahertz wave energy dissipator according to the present invention, which specifically includes the following steps: S101. Prepare a flexible mesoporous elastomeric substrate.

[0078] The specific steps include: selecting balsa wood (Ochroma pyramidale) as the natural plant stem raw material, and cutting it into block samples with dimensions of 50 mm × 50 mm × 10 mm. The samples are placed in a 2 wt% sodium chlorite (NaClO2) aqueous solution, the pH is adjusted to 4.5 with glacial acetic acid, and treated in an 80℃ water bath for 6 hours to selectively remove lignin. After treatment, the samples are removed, repeatedly washed with deionized water until neutral, and then placed in a 5 wt% sodium hydroxide aqueous solution, treated at 80℃ for 2 hours to further remove hemicellulose and other components. After the above chemical treatment, the samples transform into a white cellulose skeleton, which is thoroughly washed with deionized water and finally placed in a freeze dryer and dried at -50℃ and a vacuum degree below 10 Pa for 48 hours to obtain a flexible mesoporous elastomeric substrate with a through-hole multi-level pore structure. The porosity of this substrate is measured to be 97.2%, and the density is 0.025 g / cm³.

[0079] S102, Prepare functionalized mesoporous elastomeric layers.

[0080] The specific steps include: mixing reduced graphene oxide (rGO) and iron(III) oxide (Fe3O4) nanoparticles at a mass ratio of 1:2, ultrasonically dispersing them in deionized water to prepare a composite dispersion with a concentration of 2 mg / mL (based on the total mass of rGO and Fe3O4). The aforementioned flexible mesoporous elastomeric substrate is then immersed in this composite dispersion at room temperature for 12 hours, with stirring every 2 hours to ensure the dispersion fully penetrates into the hierarchical pores of the substrate. After removal, excess dispersion is gently rinsed off with deionized water, and the substrate is dried in a 60°C vacuum drying oven for 24 hours to uniformly load the conductive nanoheterogeneous material (i.e., the rGO / Fe3O4 composite) onto the pore surface, resulting in a functionalized mesoporous elastomeric layer. The loading of the conductive nanoheterogeneous material in this layer is approximately 5 wt% of the substrate mass. Due to this extremely low loading, the original high porosity and low density characteristics of the substrate are maintained.

[0081] S103. Construct a pyramidal gradient protrusion array using the ice template method.

[0082] This step specifically includes: First, a composite dispersion for the ice-template method was prepared. A small amount of the previously prepared functionalized mesoporous elastomeric layer sample was frozen in liquid nitrogen and then ground into powder. Using deionized water as a solvent, the powder was homogenized by high-speed shearing (12000 rpm, 30 minutes) to obtain a suspension of mesoporous elastomeric fiber components. The fiber length was controlled at 50-150 μm, and the concentration was adjusted to 1.0 wt%. The aforementioned rGO / Fe3O4 composite nanoparticles were added to the suspension to achieve a final concentration of 2 mg / mL. Simultaneously, 0.05 wt% sodium dodecylbenzenesulfonate was added as a dispersant. The mixture was ultrasonically dispersed in an ice-water bath for 30 minutes to obtain a uniformly suspended composite dispersion.

[0083] The functionalized mesoporous elastomeric layer obtained in step S102 was treated with oxygen plasma (vacuum 50 Pa, power 15 W, time 3 minutes) to improve surface hydrophilicity. The treated sample was placed on the cold stage of a directional freezing device, with the surface temperature of the cold stage pre-set to -40℃, and the lower surface of the sample in close contact with the cold stage. The composite dispersion was uniformly coated onto the upper surface of the sample using a scraping method, with the coating thickness controlled at 400 μm. The directional freezing program was started, with the cold stage temperature maintained at -40℃ and the ambient temperature controlled at 8℃, forming a vertical temperature gradient of approximately 20 °C / cm. Ice crystals grew directionally along the temperature gradient direction (i.e., perpendicular to the upper surface), with a growth rate of approximately 5 μm / s. During the ice crystal growth process, the mesoporous elastomeric fibers and rGO / Fe3O4 nanoparticles in the dispersion were displaced and assembled in situ along the ice crystal front, and the ice crystals themselves grew into sacrificial templates with a pyramidal morphology. After 60 minutes of complete freezing, the sample was transferred to a freeze dryer with a cold trap temperature of -55°C and a vacuum of 5 Pa. A segmented heating program was used: first, drying at -30°C for 6 hours, then increasing the temperature at 1°C / h to -10°C and holding for 4 hours, and finally increasing the temperature to 25°C and holding for 2 hours to allow the ice crystals to completely sublimate. After removing the ice crystal template, the space previously occupied by the ice crystals was transformed into pores, while the mesoporous elastomeric fibers and rGO / Fe3O4 nanoparticles assembled in the ice crystal gaps remained, forming an in-situ pyramidal gradient protrusion array on the upper surface of the functionalized mesoporous elastomeric layer that is homologous to the matrix and has continuous fiber penetration.

[0084] Scanning electron microscopy revealed that the obtained pyramidal gradient protrusions are regular square pyramids with a diameter of approximately 250–300 μm and a height of approximately 350–400 μm. The array period (i.e., the distance between the centers of the bases of adjacent square pyramids) is 1.2–1.4 times the diameter of the base circumcircle. The pyramids have sharp apexes and smooth sides. Energy dispersive spectroscopy (EDS) analysis showed that the conductive nanomaterial loading at the apex of the pyramids was low, while the loading at the bottom was high, exhibiting a continuous gradient increase from top to bottom. Furthermore, due to the slight non-uniformity of the temperature field on the cold stage, the height of the pyramids at different locations in the array gradually increases from one side to the other, further enhancing the impedance gradient effect at the array level.

[0085] S104. The lower surface of the functionalized mesoporous elastomeric layer with the pyramidal gradient protrusion array is combined with the open-cell flexible polymer pad layer to form an integrated composite structure.

[0086] This step specifically includes: selecting open-cell melamine-formaldehyde foam as the flexible polymer padding layer, with a density of 0.022 g / cm³, a compression resilience of 92%, and a thickness of 3 mm. The lower surface of the aforementioned functionalized mesoporous elastomeric layer with a pyramidal gradient protrusion array is aligned with the foam padding layer, and a hot-pressing fusion process is used for bonding: hot-pressing at 120℃ and 0.2 MPa for 5 minutes allows the mesoporous elastomeric layer and the foam padding layer to form an integrated composite structure through hot-melt bonding.

[0087] S105. Post-processing of the integrated composite structure.

[0088] The specific steps include: treating the integrated composite structure obtained in step S104 in a vacuum drying oven at 80°C for 12 hours to remove residual moisture and volatiles; then depositing perfluorodecyltrimethoxysilane on the surface in vapor phase to form a hydrophobic modification layer, improving environmental stability, and finally obtaining the terahertz wave energy dissipator.

[0089] After obtaining the final terahertz energy dissipator, its vertical incident reflection loss was tested using a terahertz time-domain spectroscopy system (frequency band 0.1~5.0 THz). The results showed an average power attenuation rate of 93% in the 1~4 THz frequency band, with a peak attenuation rate of 97% at 2.5 THz. Mechanical performance tests showed that the dissipator could withstand 60% compressive strain and fully rebound after compression; it could be bent into an arc with a radius of 5 mm without pyramidal cracking or interlayer separation; after 1000 cycles of 50% compressive strain, the structure remained intact, and the electromagnetic performance attenuation was less than 4.5%.

[0090] Example 2 The results are basically the same as in Example 1, except that some materials and process parameters have been adjusted, as follows: In step S101, poplar (Populus sp.) was selected as the raw material, and the delignification treatment conditions were adjusted as follows: sodium chlorite concentration of 2.5 wt%, pH value of 4.0, treatment at 85℃ for 8 hours; sodium hydroxide concentration of 6 wt%, treatment at 85℃ for 3 hours. The resulting mesoporous elastomeric substrate had a porosity of 96.8% and a density of 0.031 g / cm³.

[0091] In step S102, a composite of carbon nanotubes (CNTs) and iron oxide (Fe2O3) nanoparticles (mass ratio 1:1) was selected, the concentration of the impregnation dispersion was 3 mg / mL, and the impregnation time was 24 hours. The density of the functionalized mesoporous elastomeric layer after loading was 0.035 g / cm³.

[0092] In step S103, the concentration of the mesoporous elastomeric fiber component in the composite dispersion is adjusted to 0.8 wt%, and the CNT / Fe2O3 concentration is 3 mg / mL. The coating film thickness is 500 μm. Directional freezing parameters: cold stage temperature -50℃, ambient temperature 5℃, temperature gradient approximately 25 °C / cm, and ice crystal growth rate approximately 3 μm / s. The resulting pyramidal gradient protrusions are regular hexagonal pyramids with a base circumcircle diameter of approximately 400~450 μm, a height of approximately 500~550 μm, and an array period (i.e., the distance between the centers of the bases of adjacent regular hexagonal pyramids) of 1.5~1.7 times the base circumcircle diameter.

[0093] In step S104, the flexible padding layer is made of open-cell polyurethane foam with a density of 0.018 g / cm³ and a compression resilience of 95%. The interface fusion adopts an adhesive process: a water-based polyurethane adhesive (30% solid content) is uniformly coated on the lower surface of the mesoporous elastomeric layer, bonded to the foam padding layer, and cured at room temperature for 24 hours.

[0094] Further testing showed that the overall thickness of the dissipative body in Example 2 was 6.1 mm, and the areal density was 710 g / m². The average power attenuation rate was 91% in the 1–4 THz frequency band, with a peak attenuation rate of 94% at 3 THz. It could withstand 60% compressive strain and bending with a radius of 5 mm, and its performance decreased by approximately 4.8% after 800 cycles of compression.

[0095] Comparative Example 1 Comparative Example 1 is a comparative example of Examples 1 and 2. The difference is that Comparative Example 1 uses a compression molding method to prepare a dense tetrahedral pyramidal microwave absorbing material to replace the functionalized mesoporous elastomeric layer with the pyramidal gradient protrusion array in Example 1, and the flexible pad layer is removed. The specific steps for constructing the terahertz wave energy dissipator in Comparative Example 1 are as follows: Step S301: Prepare a mixture of silicone rubber raw material and iron powder.

[0096] The specific steps include: weighing out raw silicone rubber (vinyl-terminated polydimethylsiloxane, molecular weight approximately 600,000) and reduced iron powder according to the weight ratio. The iron powder is added to the raw silicone rubber in batches and mixed on a two-roll mill for 30 minutes to ensure the iron powder is evenly dispersed in the silicone rubber matrix. During the mixing process, a vulcanizing agent (2,5-dimethyl-2,5-di-tert-butylperoxide, 1.5 wt% of the silicone rubber mass) and an accelerator (tracene propyl isocyanurate, 0.5 wt% of the silicone rubber mass) are added sequentially, and mixing continues for 10 minutes to obtain a homogeneous mixture.

[0097] Step S302: The mixture is molded to obtain a one-piece dense square pyramidal microwave absorbing material.

[0098] This step specifically includes: filling the mixture into a stainless steel mold with a quadrangular pyramid array cavity. The mold design parameters are as follows: the quadrangular pyramids are regular quadrangular pyramids, the angle between the slant heights of two opposite sides is 15°, the pyramid height is 350 μm, the base side length is approximately 260 μm, the pyramids are continuously arranged without spacing along the base edge, the base thickness is 0.5 mm, and the overall array size is 50 mm × 50 mm. The mold is placed on a flat vulcanizing machine and hot-pressed at 150℃ and 10 MPa pressure for 15 minutes to allow the mixture to fully flow and fill the mold cavity. After hot pressing, it is cooled to room temperature while maintaining pressure, and then demolded to obtain a one-piece molded dense quadrangular pyramid microwave absorbing material.

[0099] Step S303: Post-process the integrally formed dense square pyramidal microwave absorbing material.

[0100] This step specifically includes: placing the demolded microwave-absorbing material in a 150℃ oven for secondary vulcanization for 2 hours to remove residual low-molecular-weight substances, thus obtaining the final product. This material has no flexible padding layer; the pyramid and base are integrally molded, and the material is uniform and dense.

[0101] Test results show that the overall thickness of the terahertz energy dissipator obtained in Example 3 is 0.85 mm (base thickness is 0.5 mm, pyramid height is 0.35 mm), and the areal density is calculated to be approximately 1850 g / m² (silicone rubber density is approximately 1.1 g / cm³, iron powder density is approximately 7.8 g / cm³, and the composite material density is approximately 5.0 g / cm³ with 70 wt% iron powder). Its perpendicular incident reflection loss was tested using a terahertz time-domain spectroscopy system, and the results show an average power attenuation rate of 91% in the 1–4 THz frequency band, which is basically equivalent to that of Example 1.

[0102] Mechanical property tests show that the material is hard and brittle: in bending tests, cracks appear at the root of the pyramid when the bending radius is less than 50 mm; in compression tests, permanent deformation occurs after applying about 30% strain, and it cannot spring back; it cannot achieve 60% compressive strain or a 5 mm radius bend. Due to the hardness and brittleness of the material, repeated compression cycle tests cannot be performed (it fails on the first compression).

[0103] As can be seen, Examples 1 and 2 using the method of the present invention, while maintaining terahertz absorption performance comparable to the prior art, significantly reduced the areal density (by more than 60%) and achieved excellent flexibility and durability under repeated deformation, which cannot be achieved by the dense molded pyramidal material prepared by Comparative Example 1 using the prior art method.

[0104] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention's specification and drawings under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.

Claims

1. A terahertz wave energy dissipator based on a pyramidal gradient protrusion array, characterized in that, include: A functionalized mesoporous elastomeric layer includes a flexible mesoporous elastomeric substrate and a conductive nanomaterial heterostructure; the flexible mesoporous elastomeric substrate has a through-hole multi-level pore structure with a porosity greater than 96% and a density of 0.015~0.05 g / cm³; the conductive nanomaterial heterostructure is uniformly loaded on the pore surface of the substrate. The pyramidal gradient protrusion array includes multiple pyramidal gradient protrusions arranged in a periodic array; the pyramidal gradient protrusion array is formed in situ on the upper surface of the functionalized mesoporous elastomeric layer by ice template method, and is an integrated composite structure homologous to the functionalized mesoporous elastomeric layer. A pre-formed open-cell flexible polymer pad is laminated onto the lower surface of the functionalized mesoporous elastomeric layer through an interface fusion process.

2. The terahertz wave energy dissipator based on a pyramidal gradient protrusion array according to claim 1, characterized in that, The mesoporous elastomeric substrate is obtained from natural plant stems through delignification treatment; the natural plant stems are balsa wood or poplar wood.

3. The terahertz wave energy dissipator based on a pyramidal gradient protrusion array according to claim 1, characterized in that, The conductive nanoheteromaterial is one or more combinations of carbon two-dimensional nanosheets, one-dimensional carbon nanotubes, conductive polymer nanoparticles, and ferrite nanoparticles.

4. The terahertz wave energy dissipator based on a pyramidal gradient protrusion array according to claim 3, characterized in that, The conductive nanoheteromaterial is a composite of reduced graphene oxide and iron oxide nanoparticles, wherein the mass ratio of reduced graphene oxide to iron oxide nanoparticles is 1:2; or The conductive nanoheteromaterial is a composite of carbon nanotubes and iron oxide nanoparticles, with a mass ratio of 1:1 between the carbon nanotubes and the iron oxide nanoparticles.

5. The terahertz wave energy dissipator based on a pyramidal gradient protrusion array according to claim 1, characterized in that, The pyramidal gradient protrusion is a regular square pyramid or a regular hexagonal pyramid, with a base circumcircle diameter of 100~500μm and a height of 150~600μm; the array period of the pyramidal gradient protrusion array is the distance between the centers of the bases of adjacent pyramidal gradient protrusions, and the array period is 1.1~1.8 times the base circumcircle diameter of the pyramidal gradient protrusion.

6. The terahertz wave energy dissipator based on a pyramidal gradient protrusion array according to claim 1, characterized in that, The open-cell flexible polymer pad is melamine formaldehyde foam or polyurethane foam; its density is less than 0.025 g / cm³; and its compression resilience is greater than 90%.

7. The terahertz wave energy dissipator based on a pyramidal gradient protrusion array according to claim 1, characterized in that, The terahertz wave energy dissipator has an overall thickness of 2-8 mm, a surface density of less than 800 g / m², an average power attenuation rate of more than 90% for vertically incident waves in the 0.5-3.5 THz frequency band, and can withstand 60% compressive strain or a minimum bending radius of 5 mm.

8. A method for constructing a terahertz wave energy dissipator based on a pyramidal gradient protrusion array as described in any one of claims 1 to 7, characterized in that, Includes the following steps: Prepare a flexible mesoporous elastomeric substrate with a through-hole multi-level pore structure; The flexible mesoporous elastomeric substrate is immersed in a dispersion medium containing conductive nanoheterogeneous material with deionized water as solvent for a predetermined time and then dried to form a uniformly loaded nanoheterogeneous functional phase on the surface of the multi-level pore structure, thereby obtaining a functionalized mesoporous elastomeric layer; wherein the concentration of conductive nanoheterogeneous material in the dispersion medium is 0.5~5 mg / mL. A pyramidal gradient protrusion array is constructed on the upper surface of the functionalized mesoporous elastomeric layer using an ice template method; the pyramidal gradient protrusion array comprises multiple pyramidal gradient protrusions arranged in a periodic array. Through interface fusion technology, the lower surface of the functionalized mesoporous elastomeric layer with the pyramidal gradient protrusion array is combined with the pre-formed open-cell flexible polymer pad to form an integrated composite structure. The integrated composite structure is post-processed, including surface modification and configuration stabilization, to obtain the terahertz wave energy dissipator.

9. The construction method according to claim 8, characterized in that, Fabrication of a flexible mesoporous elastomeric substrate with a through-hole hierarchical pore structure includes: Natural plant stems are selected and subjected to delignification and drying processes to obtain the flexible mesoporous elastomeric substrate. When the selected natural plant stem is balsa wood, the delignification treatment and drying include: The pH of a sodium chlorite aqueous solution with a mass fraction of 1.5~2.5wt% was adjusted to 4.5 using glacial acetic acid. The natural plant stems were then added to the adjusted sodium chlorite aqueous solution and treated in a water bath at 75~85℃ for 5.5~6.5h. After treatment, the stems were removed and repeatedly washed with deionized water until neutral to obtain the pre-treated substrate. The pretreated substrate is added to a sodium hydroxide aqueous solution with a mass fraction of 4.5~5.5wt%, and treated in a water bath at 75~85℃ for 1.5~2.5h. After treatment, the substrate is removed, washed with deionized water, and dried to obtain the flexible mesoporous elastomeric substrate.

10. The construction method according to claim 8, characterized in that, The process of immersing the flexible mesoporous elastomeric substrate in a dispersion medium containing conductive nanomaterials using deionized water as a solvent for a predetermined time and then drying it includes: The flexible mesoporous elastomeric substrate is immersed at room temperature in a dispersion medium containing conductive nano-heterogeneous material with deionized water as solvent for 12-24 hours, and is stirred once every 1.5-2.5 hours during the immersion process to obtain the immersed substrate. After rinsing the surface of the impregnated substrate to remove the surface liquid, vacuum dry it at a temperature of 50~70℃ for 20~24h.

11. The construction method according to claim 8, characterized in that, A pyramidal gradient protrusion array is constructed on the upper surface of the functionalized mesoporous elastomeric layer using the ice template method, including: The flexible mesoporous elastomeric substrate is subjected to high-speed shearing and homogenization treatment to obtain fiber components; The fiber component and the conductive nanoheterosome were dispersed in deionized water to obtain a uniformly suspended composite dispersion. The upper surface of the functionalized mesoporous elastomeric layer is subjected to plasma activation pretreatment, and then the composite dispersion is uniformly coated onto the upper surface of the pretreated functionalized mesoporous elastomeric layer by a scraping method to form a liquid film of a preset thickness. The coated functionalized mesoporous elastomeric layer is placed on a cold stage with a vertical temperature gradient, so that ice crystals grow in a direction perpendicular to the upper surface of the functionalized mesoporous elastomeric layer. During the ice crystal growth process, the fiber component and the conductive nano heterostructure are assembled in situ along the ice crystal front to form a pyramidal ice template. The pyramidal ice template is freeze-dried and sublimated to remove ice crystals from the pyramidal ice template, so as to form a homogeneous pyramidal gradient protrusion array in situ on the upper surface of the functionalized mesoporous elastomeric layer.

12. The construction method according to claim 11, characterized in that, In the composite dispersion, the concentration of the mesoporous elastomeric fiber component is 0.5-2 wt%. % The concentration of the nano-heterogeneous functional phase is 0.5-5 mg / mL; sodium dodecylbenzenesulfonate is also added to the composite dispersion as a dispersant at an amount of 0.05 wt%. The temperature gradient for directional growth is 10-30 °C / cm, the cold stage temperature is -20 °C to -80 °C, and the ice crystal growth rate is 1-10 μm / s; The preset thickness of the liquid film is 200-800 μm; The freeze-drying process employs a segmented heating program with a vacuum level below 10 Pa and a cold trap temperature below -50 °C.